2016
DOI: 10.1002/jbmr.3059
|View full text |Cite
|
Sign up to set email alerts
|

BMI-1 Mediates Estrogen-Deficiency–Induced Bone Loss by Inhibiting Reactive Oxygen Species Accumulation and T Cell Activation

Abstract: Previous studies have shown that estrogen regulates bone homeostasis through regulatory effects on oxidative stress. However, it is unclear how estrogen deficiency triggers reactive oxygen species (ROS) accumulation. Recent studies provide evidence that the B lymphoma Mo-MLV insertion region 1 (BMI-1) plays a critical role in protection against oxidative stress and that this gene is directly regulated by estrogen via estrogen receptor (ER) at the transcriptional level. In this study, ovariectomized mice were g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 47 publications
(130 reference statements)
6
32
0
Order By: Relevance
“…(18) Oxidative stress levels of osteon structures are increased with age (36) and mouse models of osteoporosis are usually accompanied by increased oxidative stress. (37) In the current study, our results suggest that overexpression of Bmi1 in MSCs corrects 1,25(OH) 2 D 3 deficiency-induced bone loss by inactivating p16 and p19 pathways, suppressing oxidative stress and DNA damage and reducing bone cell senescence and SASP. Nevertheless, the detailed mechanism whereby Bmi1 inhibits oxidative stress needs to be further determined.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…(18) Oxidative stress levels of osteon structures are increased with age (36) and mouse models of osteoporosis are usually accompanied by increased oxidative stress. (37) In the current study, our results suggest that overexpression of Bmi1 in MSCs corrects 1,25(OH) 2 D 3 deficiency-induced bone loss by inactivating p16 and p19 pathways, suppressing oxidative stress and DNA damage and reducing bone cell senescence and SASP. Nevertheless, the detailed mechanism whereby Bmi1 inhibits oxidative stress needs to be further determined.…”
Section: Discussionsupporting
confidence: 55%
“…It has been reported that abnormal ROS elevation occurs in Bmi1 knockout mice, and N‐acetylcysteine (NAC) supplementation may correct the premature aging phenotype of Bmi1 null mice . Oxidative stress levels of osteon structures are increased with age and mouse models of osteoporosis are usually accompanied by increased oxidative stress . In the current study, our results suggest that overexpression of Bmi1 in MSCs corrects 1,25(OH) 2 D 3 deficiency‐induced bone loss by inactivating p16 and p19 pathways, suppressing oxidative stress and DNA damage and reducing bone cell senescence and SASP.…”
Section: Discussionsupporting
confidence: 52%
“…In this study, we noted that Bmi1 overexpression in MSCs could not rescue completely Bmi1 global deficiency‐induced skeletal growth retardation and osteoporotic phenotypes, although it can accelerate skeletal growth and osteoblastic bone formation through stimulating the osteogenesis of BM‐MSCs in WT mice. It may be related to Bmi1 gene widely expression in embryonic stem cells, placenta, thymus, heart, testicles, and brain , especially, not only in MSCs , but also in lymphocytes . Our previous findings demonstrate that overexpression of Bmi1 only in lymphocytes stimulates osteogenesis of BM‐MSCs by releasing osteogenic factors and lowering ROS levels, thereby accelerating osteogenic bone formation , suggesting that overexpression of Bmi1 in lymphocytes can improve the osteogenic microenvironment and stimulate osteogenesis.…”
Section: Discussionmentioning
confidence: 90%
“…42,43 We recently also demonstrated that B lymphoma Mo-MLV insertion region 1 (Bmi-1) overexpression in lymphocytes can protect against estrogen deficiency-induced osteoclastogenesis and bone loss by inhibiting oxidative stress, T cell activation, and receptor activator of nuclear factor-kappa B ligand (RANKL) production. 44 It has been reported that VDR has an effect on potent osteoclastogenic cytokines, including IL-1, in vitro. 45 These cytokines not only influence systemic bone remodeling but also act locally to compromise the tissue response to periodontal diseases.…”
Section: Discussionmentioning
confidence: 99%